Navigating Power and Claiming Justice: Tenant Experiences at Saskatchewan’s Housing Law Tribunal - Buhler, Sarah; Tang, Rachel (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2019)
This article discusses a qualitative interview project where twenty tenants shared their experiences about having hearings at the Office of Residential Tenancies [the ORT], Saskatchewan’s housing law tribunal.  The interviews provide insights into housing problems faced by tenants, their experiences with self-representation at the ORT, and their reflections about the outcomes of their cases.  We analyze how tenants prepared for their hearings, their experiences of the hearing process, and their perceptions of fairness throughout the process.  We then discuss participants’ assessments of whether they received “justice” at the ORT. The interviews illuminate the ways that the same patterns of power and inequality that produce housing problems in the first place persist but are also occasionally interrupted and exposed in the housing tribunal process.  They show also that tenants use the ORT to make important claims about justice and to resist landlord power in the face of larger patterns of inequality and exploitation.